Measurement of Partial Discharge Inside Metal Enclosed Power Apparatus using Internal Sensor - Umar Khayam; Yushan Yushan (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Partial discharge detection by detecting the released energy in form of electromagnetic wave during discharge using Ultra-High Frequency (UHF) antenna is one method to determine insulation system quality in high voltage system. UHF PD detection method has several advantages over conventional PD detection system such as IEC 60270 method. The advantages of UHF PD detection system are the capability to directly detect PD signal without firstly shut down, the installation system and their immunity from environmental noise. Nowadays most of electrical equipment are in form of metal enclosed model. This paper deals with measurement of PD occurrences inside metal enclosed equipment using internal sensor. The loop antenna is used for PD measurement. The experimental results show that the presence of metal box gives significant change on the PD signal detected by using loop antenna. Without metal box, the measurement sensitivity decreases because of the high level of background noise. The metal box acts as electromagnetic wave shielding and reduces the external noise. When the loop antenna placed inside metal box, the measurement sensitivity increases because of the low level of background noise inside metal box.